“SURVIVAL IS NOT A CHOICE, BUT A NECESSITY FOR GROWTH”: EXPLORING WOMENPRENEUR ADAPTATION STRATEGIES IN TIMES OF UNCERTAINTY WHEN FACING CRISIS - Ayi Fathimatus Zahro; Iing Sri Hadiningrum (SOSIOEDUKASI, 2025)
This research aims to explore womenpreneur adaptation strategies in facing crisis situations using a phenomenological approach. Data was obtained through in-depth interviews and then analyzed to reveal subjective experiences, adaptation patterns, and meanings constructed in their entrepreneurial journey. Research results show that womenpreneurs develop multidimensional adaptive strategies, including business innovation based on sustainability values, utilization of social networks and communities, and psychological resilience in managing dual-role pressures. These findings confirm that womenpreneurs not only survive, but make crises a momentum to grow and strengthen their entrepreneurial identity. The research contribution lies in enriching womenpreneurship literature through in-depth qualitative perspectives, as well as practical implications for formulating women empowerment policies, entrepreneurship training programs, and economic inclusion strategies that are more sensitive to the real needs and challenges of women business owners.